Creating a Nationality The Ramjanmabhumi Movement and Fear of the Self - Nandy, Ashis...[et.al] (New Delhi, 2000)
The destruction of the Babri Masjid at Ayodhya in December 1992 was a watershed in the politics of independent India. It was also an apocalyptic turning-point for community life at Ayodhya, and for the highly interdependent cultural lives of Hindus and Muslims living there. This book narrates how Ayodhya's inhabitants experienced the events that led up to and followed the destruction of the mosque
Keywords: Communalism